New metropolitan discipline: Foundational significance of Madrid 2016 Plan - Contin, Antonella; B. Ortiz, Pedro (Urban, 2016)
Introduction Madrid 2016; a new concept for a qualitative metropolis. Madrid 2016 Plan, by the late ‘90s, tried to set up the foundation of a new urban practice from a metaphor or a discursive practice, in the line of the Bidagor 1946’s Madrid Plan. The history of that Plan shows that if we talk about quality, notwithstanding the big job to be done educating human perceptions and emotions, we are opening the eyes to the capacity and awareness to feel the city. This requires an evaluation, a judgment in the ethic and aesthetic dimension and not just the simple education of senses and intellect. That is, if we want to be “worthy of our time”; a time that has dried out dimensions for reflection, which is reduced to trivial communication. Moreover, it has dried up the gestalt’s capture by which you sense, before you even know what is good and what is not. Keywords Metropolitan Architecture; Metro Matrix; Madrid 2016 Plan; Mental Map